New Quasi-Newton (Dfp) With Logistic Mapping - Shareef, Salah G.; Fathi, Bayda G. (Science Journal of University of Zakho, 2016)
In this paper, we propose a modification of the self-scaling quasi-Newton (DFP) method for unconstrained optimization using logistic mapping. We shoe that it produces a positive definite matrix. Numerical results demonstrate that the new algorithm is superior to standard DFP method with respect to the NOI and NOF.